Globally significant oceanic source of organic carbon aerosol - Dominick V. Spracklen; Steve R. Arnold; Jean Sciare; Kenneth S. Carslaw; Casimiro Pio (Geophysical Research Letters)
Significant concentrations of organic carbon (OC) aerosol are observed at three oceanic surface sites (Amsterdam Island, Azores and Mace Head). Two global chemical transport models (CTMs) underpredict OC concentrations at these sites (normalised mean bias of −67% and −58%). During periods of high biological activity monthly mean concentrations are underpredicted by a factor of 5–20. At Amsterdam Island and Mace Head, observed OC correlates well (R2 = 0.61–0.77) with back‐trajectory weighted chlorophyll‐a, suggesting an oceanic OC source driven by biological activity. We use a combination of remote sensed chlorophyll‐a, back trajectories and observed OC to derive an empirical relation between chlorophyll‐a and the total oceanic OC emission flux. Using the GEOS‐chem CTM we show a global oceanic OC emission, from primary and secondary sources, of ∼8 Tg/year matches observations. This emission is comparable in magnitude to the fossil fuel OC source and increases the simulated global OC burden by 20%.